Investigating the Photocatalytic Degradation of Oil Paint using ATR-IR and AFM-IR - Morsch, Suzanne; van Driel, Birgit A; van den Berg, Klaas Jan; Dik, Joris (ACS applied materials & interfaces, 2017)
As linseed oil has a longstanding and continuing history of use as a binder in artistic paints, developing an understanding of its degradation mechanism is critical to conservation efforts. At present, little can be done to detect the early stages of oil paint deterioration due to the complex chemical composition of degrading paints. In this work, we use advanced infrared analysis techniques to investigate the UV-induced deterioration of model linseed oil paints in detail. Subdiffraction limit infrared analysis (AFM-IR) is applied to identify and map accelerated degradation in the presence of two different grades of titanium white pigment particles (rutile or anatase TiO ). Differentiation between the degradation of these two formulations demonstrates the sensitivity of this approach. The identification of characteristic peaks and transient species residing at the paint surface allows infrared absorbance peaks related to degradation deeper in the film to be extricated from conventional ATR-FTIR spectra, potentially opening up a new approach to degradation monitoring.